The Use of Maps in Turkish Newspapers. Issue 4 (3rd July 2016) - Demirci, Ali; Suslu, Zeliha
Abstract: This study analyzes the use of maps in Turkish newspapers in order to evaluate their potential to contribute to the enhancement of geographic knowledge in society. This study reviewed the content of three Turkish newspapers published between January 2008 and August 2012. Only 835 maps were used in the newspapers during the study period, or an average of 278 maps per newspaper. During the study period, about 15, 720 news articles were published per month in the three newspapers; however, only five of these were illustrated with a map. The study reveals the potential for Turkish newspapers to increase society's geographic awareness with additional published maps.